Dimming the “Halo” Around Monogamy: Re-assessing Stigma Surrounding Consensually Non-monogamous Romantic Relationships as a Function of Personal Relationship Orientation - Balzarini, Rhonda N.; Shumlich, Erin J.; Kohut, Taylor; Campbell, Lorne (Frontiers in Psychology, 2018)
Previous research suggests that both monogamous and consensually non-monogamous (CNM) participants rate monogamous targets more positively. However, this pattern of stigma toward CNM relationships and the “halo effect” surrounding monogamy is at odds with the view that people typically favor members from their own groups over members of other groups. In the current research, we sought to re-examine the halo effect, using a more direct measure of stigma (i.e., desired social distance), in a methodological context that differentiates between the three most common types of CNM relationships. A convenience sample (N = 641) of individuals who self-identified as monogamous (n = 447), open (n = 80), polyamorous (n = 62), or swinger (n = 52) provided social distance ratings in response to these same relationship orientations in a counterbalanced order. Congruent with prior findings, CNM participants favored monogamous targets over CNM targets as a broad category (replicating the halo effect). However, results indicated this effect dissipated when participants were asked to differentiate between relationships they identify with, and other CNM relationships. Furthermore, supplementary findings suggest that monogamous targets were perceived to be the least promiscuous and were associated with the lowest perceived sexually transmitted infection (STI) rates, while swinger targets were perceived as the most promiscuous and were associated with the highest perceived STI rates. Consequently, our results imply social distance is partly attributable to the perception of STI risk, but not perceptions of promiscuity.